Effect of dietary flavonoids on hepatic CYP2E1 and 3A4 activity : implication for food-drug interactions - Östlund, Johanna (SLU/Dept. of Food Science, 2017)
Flavonoids are a group of phytochemicals ubiquitously present in vegetables, fruits, berries and herbs. It is suggested that they contribute to protection against several lifestyle diseases including cancer. Nevertheless, herbal extracts and foods rich in certain flavonoids have been shown to interact with the metabolism of drugs that may cause adverse effects. The interac-tions are often due to modulation of drug metabolising cytochrome P450 enzymes in the liver. The present study examined inhibitory effects of the flavonoid quercetin on the cyto-chrome P450 isoform CYP2E1. Quercetin, myricetin and isorhamentin were flavonoids inves-tigated for inhibitory effects on the isoform CYP3A4. The metabolising function of those spe-cific cytochrome P450 isoforms is crucial for detoxification and/or bioactivation of foreign compounds. Catalytic activity was measured in vitro using human liver microsomes separated in male and female pools. Reversibility of enzyme inhibition was investigated and kinetic measurements were performed in order to determine inhibition mechanism. Based on results from animal experiments, the hypothesis was that the selected flavonoids inhibit enzyme ac-tivity and that the degree of inhibition differed between genders. Quercetin inhibited CYP2E1 activity and quercetin and myricetin inhibited CYP3A4 activ-ity as expected, but isorhamnetin had no inhibitory effects on CYP3A4. Inhibition was re-versible in all enzyme pools, but the mechanism varied between competitive, uncompetitive and non-competitive inhibition. These observations are related to the flavonoid structure where the number and position of hydroxyl-groups determine the binding mechanism to the enzyme and thereby the level and mode of inhibition. Surprisingly, this study revealed no sub-stantial gender disparities of flavonoid inhibition in human cytochrome P450 activity. Large variations between enzyme pools were observed within the same gender, suggesting inter-in-dividual differences attributable to genetic and/or other lifestyle factors rather than gender. This study provided gained insight in human cytochrome 450 regulation in presence of fla-vonoids and the results can contribute to research in drug development.